2007
DOI: 10.1128/aem.02958-06
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reductive Dechlorination of Aroclor 1260 in Baltimore Harbor Sediment Microcosms Is Catalyzed by Three Phylotypes within the Phylum Chloroflexi

Abstract: The specific dechlorination pathways for Aroclor 1260 were determined in Baltimore Harbor sediment microcosms developed with the 11 most predominant congeners from this commercial mixture and their resulting dechlorination intermediates. Most of the polychlorinated biphenyl (PCB) congeners were dechlorinated in the meta position, and the major products were tetrachlorobiphenyls with unflanked chlorines. Using PCR primers specific for the 16S rRNA genes of known PCB-dehalogenating bacteria, we detected three ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
112
7
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 68 publications
12
112
7
2
Order By: Relevance
“…These isolates are unified by their ability to grow via organohalide respiration, that is, they use halogenated organic compounds as terminal electron acceptors while using hydrogen as an electron donor in an anaerobic respiration (Tas et al, 2010). In addition, other relatively closely related DEH, including some marine phylotypes, have been implicated in organohalide respiration by enrichment or stable-isotope probing experiments Watts et al, 2005;Bedard et al, 2007;Fagervold et al, 2007;Kittelmann and Friedrich 2008a, b). Nevertheless, there are numerous 16S rRNA gene sequences within the whole DEH clade that are considerably divergent from these organohalide-respiring organisms.…”
Section: Introductionmentioning
confidence: 99%
“…These isolates are unified by their ability to grow via organohalide respiration, that is, they use halogenated organic compounds as terminal electron acceptors while using hydrogen as an electron donor in an anaerobic respiration (Tas et al, 2010). In addition, other relatively closely related DEH, including some marine phylotypes, have been implicated in organohalide respiration by enrichment or stable-isotope probing experiments Watts et al, 2005;Bedard et al, 2007;Fagervold et al, 2007;Kittelmann and Friedrich 2008a, b). Nevertheless, there are numerous 16S rRNA gene sequences within the whole DEH clade that are considerably divergent from these organohalide-respiring organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Retaining a fourth end-member improved the fit of these two congeners and resulted in an end-member that suggested evidence of a small amount of dechlorination in a few HPS samples. Other studies have reported preferential enrichment of PCB 49 and PCB99 in studies of dechlorination of Aroclor 1260 in estuarine environments (Fagervold et al, 2007). A hint of this can be seen in Figure 15 where PCB49 and PCB99 are elevated in the modeled EndMember 3 bar chart fingerprint when compared to the homogenized mixture of Aroclors 1260/1254/1248 shown directly below.…”
Section: Step 5: Advanced Chemical Fingerprinting (Acf)mentioning
confidence: 55%
“…Fagervold (2007) reported that three different phylotypes within the Chloroflexi increased in response to Aroclor 1260 in Baltimore Harbor sediment, suggesting that a consortium of dechlorinating bacteria with various specificities may result in more extensive dechlorination of mixed PCBs. In addition to the above studies, the tetrachloroethene dehalorespirer, Dehalococcoides ethenogenes strain 195, dechlorinated 2,3,4,5,6-PCB (Fennell et al, 2004), although growth was not tested.…”
Section: Introductionmentioning
confidence: 99%
“…Effective, economical methods for remediation of PCB contaminated sediments are lacking, however, progress has been made in understanding potential for biotransformation of PCBs in recent years. Discovery that anaerobic bacteria of the phylum Chloroflexi, including the genus Dehalococcoides and more distantly-related taxons, can dechlorinate PCBs may offer a promising avenue for bioremediation (Wu et al, 2000;Cutter et al, 2001;Fennell et al, 2004;Watts et al, 2005;Fagervold et al, 2005;Fagervold et al, 2007;Bedard et al, 2007;May et al, 2008;; and see review by Bedard, 2008). In this study we evaluated whether stimulating native Dehalococcoides populations or bioaugmentation could increase dechlorination of low concentrations of weathered PCBs, and whether the treatment effects persist over a relatively long time frame (> 1 year).…”
Section: Introductionmentioning
confidence: 99%